PENINGKATAN EFEKTIVITAS PENGOLAHAN AIR LIMBAH PROSES PEMUTIHAN PULP DENGAN REAKTOR UP-FLOW ANAEROBIC SLUDGE BLANKET (UASB) DAN LUMPUR AKTIF TERMOBILISASI (INCREASING THE EFFECTIVITY PULP BLEACHING PROCESS EFFLUENT TREATMENT BY UP-FLOW ANAEROBIC SLUDGE BLANKET (UASB) AND MOBILIZED ACTIVATED SLUDGE REACTORS) - Yusup Setiawan; Sri Purwati; Rina S Soetopo; Kristaufan Joko Pramono (Center for Pulp and Paper, 2008)
Treatment of pulp bleaching effluent using upflow anaerobic sludge blanket (UASB) and suspended carrier Biofilm (SCB) system have been carried out. Upflow Anaerobic Sludge Blanket (UASB) and suspended carrier Biofilm (SCB) reactors were run on the Hydraulic Retention Time (HRT) of 12 hours, respectively. Micronutrient solution containing some traces elements was added into feed wastewater of UASB reactor to accelerate the growth of granular sludge. Sludge characteristics of UASB and activated sludge reactors were observed and analyzed. Settling rate of granular sludge in UASB reactors was also mesured. Effluent of UASB reactor was treated further in Suspended Carrier Biofilm (SCB) reactor.Concentration of COD, TSS and AOX parameters both influent and effluent of UASB reactor as well as suspended carrier biofilm (SCB) reactor were analyzed. Result revealed that UASB reactor run on the Hydraulic Retention Time (HRT) of 12 hours could remove COD up to 90%, TSS up to 91% and AOX up to 84%. Addition of micronutrient solution has accelerated the growth of granular sludge. Dark-brownesh color of granular sludge with the diameter of 1-4 mm having settling rate of 70-120 m/hr has been formed. SCB reactor as post treatment could remove COD of 85%, TSS of 73% and AOX of 76%. Sequential UASB and SCB reactor could increase the effectivity of pulp and paper mill wastewater treatment with the removal of dissolved and suspended organic pollutant more than 94%.Key words: AOX, COD, activated sludge, granular sludge, UASB.INTISARI Pengolahan air limbah proses pemutihan pulp dengan system Upflow Anaerobic Sludge Blanket (UASB) dan lumpur aktif termobilisasi telah dilakukan. Reaktor (UASB) dan lumpur aktif termobilisasi masin-masing dioperasikan pada waktu tinggal 12 jam. Larutan micronnutrisi yang mengandung ion-ion logam dalam jumlah sedikit ditambahkan ke dalam umpan reactor UASB untuk mempercepat pertumbuhan lumpur granul. Karakteristik lumpur reaktor UASB diamati dan dianalisa. Kecepatan pengendapan lumpur granul juga diukur. Efluen reactor UASB diolah lebih lanjut dalam reactor lumpur aktif termobilisasi. Parameter COD, TSS dan Adsorbable Organic Halies (AOX) menunjukan bahwa pada waktu tinggal 12 jam, reaktor UASB dapat mereduksi COD 90%, TSS 91% dan AOX 84%. Penambahan larutan mikronutrisi berpengaruh signifikan terhadap pertumbuhan mikroganisme dalam membentukan lumpur granul. Lumpur granul yang terbentuk berdiameter 1-4 mm berwarna hitam kecoklatan memiliki kesepatan 70-120 m/jam. Pengolahan lanjutan dengan sistem lumpur aktif termobilisasi masing-masing dapat mereproduksi COD 85%, TSS 73% dan AOX 76%. Sistem pengolahan air limbah gabungan rector UASB dan lumpur aktif termobilisasi dapat meningkatkan efektifitas pengolahan air limbah industri pulp dan kertas dengan reduksi pencemar organik terlarut dan tersuspesi lebih besar dari 94%.Kata kunci : AOX, COD, lumpur aktif, lumpur granul, UASB